2022-LBA-841-ESGO Cosmetic outcome and psychosexual distress after treatment for vulvar intraepithelial neoplasia. (27th October 2022) - Trutnovsky, Gerda; Holter, Magdalena; Gold, Daniela; Kopera, Daisy; Deban, Julia; Misut, Dina; Greimel, Elfriede; Aust, Stefanie; Reich, Olaf; Tamussino, Karl
Abstract : Introduction: Treatment for vulvar intraepithelial neoplasia (VIN) may lead to anxiety concerning genital health, influence body image and sexual activity. Surgical treatment may be associated with vulvar scarring and psychosexual morbidity. Conservative medical treatments do not modify genital anatomy and may lead to better cosmetic outcome and less psychosexual distress. Methods: This is a subsequent analysis of the multicentre, randomised, phase 3, non-inferiority trial 'Topical imiquimod versus surgery for vulvar intraepithelial neoplasia' published in The Lancet in April 2022. Patients were randomized to primary topical treatment or surgery and stratified by unifocal or multifocal disease. Cosmetic outcome was assessed by three investigators blinded to group allocation. Digital photos were scored with a modified version of the Global Aesthetic Improvement Scale (GAIS).The Cervical Dysplasia Distress Questionnaire (CDDQ), the Sexual Activity Questionnaire (SAQ) and the Client Satisfaction Questionnaire (CSQ) were used to examine psychosexual distress and treatment satisfaction. Results: 110 patients aged between 19 and 82 years were enrolled. Per-protocol analysis showed complete clinical response in 80% (37/46) using imiquimod, compared to 79% (41/52) after one surgical intervention. Photo-documentation at baseline and 6 months follow-up was available for 84 of these patients (44 imiquimod, 40 surgery). Inter-rater agreement was poor (below 0.5) for the GAIS score (100%) and moderate to good (0.5 to 0.9) for lesion severity of the VASS (75%). There were no significant differences in GAIS and VASS scores between treatment groups in patients with complete (n= 66) or partial clinical response (n=18). No significant associations between cosmetic outcome, psychosocial distress, treatment satisfaction and initial lesions size of VIN could be found. Conclusions: Topical imiquimod and surgery may have similar effects on cosmetic outcome, psychosexual distress and treatment satisfaction in patients with VIN.